Identification of Cholecystokinin by Genome-Wide Profiling as Potential Mediator of Serotonin-Dependent Behavioral Effects of Maternal Separation in the Amygdala - Weidner, Magdalena T.; Lardenoije, Roy; Eijssen, Lars; Mogavero, Floriana; De Groodt, Lilian P. M. T.; Popp, Sandy; Palme, Rupert; Förstner, Konrad U.; Strekalova, Tatyana; Steinbusch, Harry W. M.; Schmitt-Böhrer, Angelika G.; Glennon, Jeffrey C.; et al. (Frontiers in Neuroscience, 2019)
Converging evidence suggests a role of serotonin (5-hydroxytryptamine, 5-HT) and tryptophan hydroxylase 2 (TPH2), the rate-limiting enzyme of 5-HT synthesis in the brain, in modulating long-term, neurobiological effects of early-life adversity. Here, we aimed at further elucidating the molecular mechanisms underlying this interaction, and its consequences for socio-emotional behaviors, with a focus on anxiety and social interaction. In this study, adult, male Tph2 null mutant (Tph2-/-) and heterozygous (Tph2+/-) mice, and their wildtype littermates (Tph2+/+) were exposed to neonatal, maternal separation (MS) and screened for behavioral changes, followed by genome-wide RNA expression and DNA methylation profiling. In Tph2-/- mice, brain 5-HT deficiency profoundly affected socio-emotional behaviors, i.e. altered emotional coping in various anxiety-related tests and decreased prosocial and increased rule breaking behavior in the resident-intruder test. Tph2+/- mice showed an ambiguous profile with context-dependent, behavioral responses. Notably, MS effects on behavior were subtle and depended on the Tph2 genotype. On the genomic level, the interaction of Tph2 genotype with MS differentially affected the expression of numerous genes, of which a subset showed an overlap with DNA methylation profiles at corresponding loci. Remarkably, changes in methylation nearby and expression of the gene encoding cholecystokinin, which were inversely correlated to each other, were associated with variations in anxiety-related phenotypes. In conclusion, next to various behavioral alterations, we identified gene expression and DNA methylation profiles to be associated with TPH2 inactivation and its interaction with MS, suggesting a gene-by-environment interaction-dependent, modulatory function of brain 5-HT availability.